Hand sanitizer gel formulations: Influence of polymer type on the rheological properties (Research, Society and Development, 2024)
COVID-19 increased the demand for alcohol-based hand sanitizer in establishments. The present study aimed to characterize different polymers and/or polymer mixtures with the potential to be used to produce alcohol-based gel hand sanitizers and evaluate the different formulations of alcohol gel as to their rheological properties. Polymers and polymer blends (natural and/or synthetic) were characterized by DSC and FTIR/NIR analysis. Six were polymers or blends of polymers efficient to production of this product in the concentration of 70% ethanol (w/w). Alcohol-based hand sanitizer gel formulations were stored at two different temperatures (25 °C and 40 °C) and subjected to rheological analysis over the storage time (0, 7, 14, and 28 days). The rheological profile indicated a behavior of pseudoplastic fluid of the samples, and they remained stable throughout the days of storage at 25 °C. Formulations containing natural polymers derived from cellulose are good alternatives to replace the carbomer gelling agent, with limitations related to the reduction of the gel apparent viscosity.